Wideband and flat-gain optical amplifier with Hafnia-bismuth erbium co-doped fiber / Alabbas Ahmed Abduljabbar Al-Azzawi - Alabbas Ahmed , Abduljabbar Al-Azzawi (2020)
A compact optical amplifier with a flat-gain characteristic is demonstrated using hafnia bismuth-erbium co-doped fiber (HB-EDF) as the gain medium. The HB-EDF was recently fabricated using a modified chemical vapor deposition (MCVD) process in conjunction with solution doping (SD) technique. The fiber has an Erbium ions concentration of 12500 wt. ppm, which was realized due to the co-doping with Hafnium and Aluminum ions. Firstly, the proposed amplifier was investigated for both single and double-pass configurations. It is found that the 0.5m long HB-EDF is the optimum length for the C-band region. For double-pass HB-EDFA, at input signal power of -10 dBm, a flat-gain of 15.9 dB was realized with a gain ripple of less than 1.4 dB, along the 45 nm wavelength region from 1525 to 1570 nm. Within the flat-gain region, the noise figure was less than 8.1 dB. Secondly, a wideband HB-EDFA was demonstrated, utilizing two short lengths of HB-EDF to fulfill amplification in both C- and L-bands. The wideband HB-EDFA was achieved using two-stage in both series and parallel structures. It is found that both parallel and backward pumping-based series HB-EDFAs obtained flat-gain characteristics over a wideband operation wavelength. For instance, in parallel HB-EDFA using 1.72 m long HB-EDF, a flat-gain of 12.1 dB was realized with a gain ripple of less than 2 dB, along the wavelength region of 80 nm from 1525 to 1605 nm. Within the flat gain region, the noise figure values vary from 6 to 11.8 dB. Besides, in backward pumping-based series HB-EDFA using 2 m long HB-EDF, a flat-gain of 14.6 dB was realized with a gain ripple of less than 2 dB, along the wavelength region of 65 nm from 1530 to 1595 nm. Within the flat-gain region, the noise figure values vary from 6.8 to 10.2 dB. Finally, a wideband and flat-gain hybrid EDFA was investigated, by employing HB-EDF and zirconia-erbium doped fiber (Zr-EDF) as a hybrid active fiber, to improve the amplification bandwidth, flat-gain, and noise figure. In parallel hybrid EDFA, at -10 dBm input signal, a flat-gain of 15.6 dB was realized with a gain ripple of less than 1 dB, along the wideband wavelength region of 75 nm from 1525 to 1600 nm. Within the flat gain region, the noise figure values vary from 4.1 to 8.7 dB. Besides, for backward pumping-based series hybrid EDFA, at input signal level of -10 dBm, a flat-gain of 14.6 dB was realized with a gain ripple of less than 1.8 dB, along the 70 nm wavelength region from 1530 to 1600 nm. Within the-flat gain region, the noise figure values vary from 4.3 to 7.9 dB. The proposed amplifiers are successfully realized not only the functional requirements but also the economically viable, by mitigation the complexity and devices used. A broadband ASE light was also successfully demonstrated to cover both C- and L bands, using the hybrid active fibers in series and parallel structures. It is found that a broader and higher ASE spectrum can be achieved at the backward pumping-based series configuration.